PA66 eight-end spinning extra-high-strength industrial yarn and preparation method thereof
By adding a modifier coupled to the nylon 66 spinning paste with a metal organic frame UiO-66-NH2 and a tannin-modified polyzobenzene modified, the problem of insufficient conformity and antistatic properties of PA66 fibers is solved. The PA66 eight-head spinning ultra-high strength industrial wire has excellent mechanical and electrical properties.
Patent Information
- Application Number
- CN202411950889.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
PA66 fiber has poor shape conformity during use, is prone to deformation and irreversible deformation, and has poor antistatic properties, which limits its application.
By coupling the metal organic frame UiO-66-NH2 with tannin-modified polyzobenzene, adding it to the nylon 66 spinning slurry, and melt extrusion spinning, PA66 8-head spinning ultra-high strength industrial silk was prepared.
It improves the mechanical properties, antistatic properties, flame retardant properties of PA66 high-strength wire, has good shape conformity and has good application prospects.
Smart Images

Figure BDA0005214844620000121 
Figure BDA0005214844620000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon, and in particular to a PA66 eight-end spun ultra-high-strength industrial yarn and a preparation method thereof. Background Art
[0002] The nylon 66 industry began to be industrialized in 1939 and is widely used in the fields of chemical fibers and engineering plastics. In particular, in the past 10 years, the world's nylon consumption has increased at an average annual rate of about 7.5%. As a type of engineering plastic, nylon is widely used in military textiles, industry, clothing, decoration, engineering plastics and other fields.
[0003] Based on the digestion and absorption of Nylstar's continuous polycondensation and direct spinning POY-DTY production technology, through the re-transformation of key equipment, exploration and optimization of production processes, we independently developed a series of ultra-fine denier nylon 66DTY fibers such as 31dtex / 23f, 44dtex / 34f, 64dtex / 68f, 78dtex / 152f, 78dtex / 168f, and successfully put them on the market. The quality level has reached or is close to that of similar brand products of European and American manufacturers, and has achieved good returns. At present, ultra-fine denier fibers have accounted for more than 30% of the company's total POY-DTY products, and the domestic market share ranks among the top.
[0004] PA66 fiber is obtained by polycondensation of ethylenediamine containing 6 carbon atoms and adipic acid containing 6 carbon atoms to obtain polyamide resin, and then melt spinning to obtain polyamide fiber; PA66 fiber molecular chain is highly ordered and regularly arranged, has excellent molecular chain orientation and crystallinity, and has intermolecular forces such as hydrogen bonds and van der Waals forces, so that it has excellent mechanical properties and good rigidity and strength. However, due to the regular molecular chain structure of PA66, fewer side chains and heterochains, fewer intermolecular forces, and the molecular chain is prone to slippage, and the fiber undergoes irreversible changes during use, making PA66 fiber poor in shape retention during use, easy to deform and produce irreversible deformation and cause creep, and its antistatic performance is poor, and static electricity is easily generated during use, which destroys the original comfort of the fiber. And the mechanical strength is low, which limits its application. Summary of the invention
[0005] The purpose of the present invention is to provide a PA66 eight-end spun ultra-high-strength industrial yarn and a preparation method thereof. The prepared PA66 eight-end spun ultra-high-strength industrial yarn has high mechanical strength and low thermal shrinkage. The modifier contains rich amino and carboxyl structures, which can form hydrogen bonds with the nylon 66 polymer structure to achieve uniform dispersion, thereby improving the mechanical properties, antistatic properties, and flame retardant properties of the nylon 66 high-strength yarn, having good shape retention, and having good application prospects.
[0006] The technical solution of the present invention is achieved in this way:
[0007] The invention provides a method for preparing a PA66 eight-end spun ultra-high-strength industrial yarn. An amino-modified metal organic framework is prepared, coupled with tannic acid-modified polyphenylene, added into a molten nylon 66 medium-high viscosity slurry, mixed evenly, melt-extruded and spun, the yarn is cooled by side-blowing air to form a yarn bundle, oiled, drawn and shaped, and wound into a yarn tube to prepare the PA66 eight-end spun ultra-high-strength industrial yarn.
[0008] As a further improvement of the present invention, the following steps are included:
[0009] S1. Preparation of UiO-66-NH2: zirconium tetrachloride and 2-aminoterephthalic acid are added to N,N-dimethylformamide, acetic acid is added, ultrasonic stirring is performed to disperse the mixture uniformly, hydrothermal reaction is performed, centrifugation is performed, washing is performed, and drying is performed to obtain UiO-66-NH2;
[0010] S2. Preparation of polyphenylene: phenol, formaldehyde and aqueous ammonia were mixed, heated to reflux with stirring, the pH value of the solution was adjusted, the reaction was continued by heating, zinc chloride was added, heated to cure, thermally cracked, crushed, and ball-milled to obtain polyphenylene;
[0011] S3. Preparation of tannic acid-modified polyphenylene: adding polyphenylene to water, adding tannic acid and a catalyst, heating and stirring the reaction, centrifuging, washing, and drying to obtain tannic acid-modified polyphenylene;
[0012] S4. Preparation of the modifier: adding tannic acid-modified polyphenylene to water, adding NHS and EDC, stirring for activation, adding UiO-66-NH2, stirring for reaction, centrifuging, washing, and drying to obtain a modifier;
[0013] S5. Solid phase viscosity enhancement and humidity control: The nylon 66 spinning grade chips are subjected to solid phase viscosity enhancement and humidity control to obtain nylon 66 medium and high viscosity chips;
[0014] S6. Melt extrusion spinning: The high viscosity slices of nylon 66 are sent to a screw extruder, a modifier is added, melt extruded, filtered, and spun through an eight-head spinning device;
[0015] S7. Cooling, oiling, drawing and shaping, and winding: The filaments are cooled by side-blowing air to form a filament bundle, oiled, drawn and shaped, and wound into a filament tube to produce PA66 eight-end spun ultra-high-strength industrial filament.
[0016] As a further improvement of the present invention, the mass ratio of zirconium tetrachloride, 2-aminoterephthalic acid and acetic acid in step S1 is 0.12-0.17:0.11-0.14:2-3, the power of the ultrasonic stirring and dispersion is 1000-2000 W, the time is 10-20 min, and the temperature of the hydrothermal reaction is 120-130 ° C, and the time is 20-24 h.
[0017] As a further improvement of the present invention, the molar ratio of phenol to formaldehyde in step S2 is 1:1-1.2, the mass ratio of ammonia water to zinc chloride is 5-7:0.5-1, the time for the heating reflux stirring reaction is 2-4 hours, the pH value of the solution is adjusted to 4-6, the time for continuing the heating reaction is 1-3 hours, the temperature of the heating curing is 65-75°C, the time is 24-28 hours, and the temperature of the thermal cracking is 1100-1200°C, and the time is 2-4 hours.
[0018] As a further improvement of the present invention, the mass ratio of the polyphenylene, tannic acid and catalyst in step S3 is 10:2-3:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 40-50° C., and the time is 3-5 hours.
[0019] As a further improvement of the present invention, the mass ratio of tannic acid-modified polyphenylene, NHS, EDC and UiO-66-NH2 in step S4 is 10-12:3-4:2-3:4-7, the stirring activation time is 20-40 min, and the stirring reaction time is 10-12 h.
[0020] As a further improvement of the present invention, the relative viscosity of the nylon 66 spinning-grade chips in step S5 is 2.2-2.3, the water content of the nylon 66 medium-high viscosity chips is 650-750 ppm, and the relative viscosity is 3.3-3.5, and the solid phase viscosity enhancement is performed on the chips at 140-170°C using nitrogen for countercurrent circulation.
[0021] As a further improvement of the present invention, the amount of the modifier added in step S6 is 3-5wt%, the temperature of the melt extrusion is 280-300°C, and the fineness of the filaments sprayed out by the spinneret is 0.03-0.05mm.
[0022] As a further improvement of the present invention, the amount of oil attached in step S7 is controlled to be 0.5-1.5%; the stretching and shaping is achieved by 1 stage preheating, 2 stages stretching, and 2 stages shaping between six pairs of hot rollers: wherein the temperature of the first pair of hot rollers is 30-40°C, the temperature of the second pair of hot rollers is 45-55°C, the first pair of hot rollers and the second pair of hot rollers preheat the silk strips, and the stretching ratio is 1-1.01 times; the winding speed is 3000-4000m / min.
[0023] The present invention further protects a PA66 eight-end spun ultra-high strength industrial yarn prepared by the above-mentioned preparation method.
[0024] The present invention has the following beneficial effects:
[0025] The present invention couples a metal organic framework UiO-66-NH2 with tannic acid-modified polyphenylene, and adds them to nylon 66 spinning slurry. UiO-66-NH2 has a high specific surface area and pore volume, so that when used as a reinforcement, it can provide more contact area to interact with the nylon matrix, which is beneficial to the diffusion of nylon molecules in its pores, increases the adhesion of the interface, and thus improves the mechanical properties of the composite material. The tannic acid-modified polyphenylene is coupled with UiO-66-NH2 through dehydration condensation, has a large specific surface area, greatly improves the dispersibility of the modifier in the nylon 66 slurry, UiO-66-NH2 has good electrical conductivity and electrostatic repulsion characteristics, enhances the electrical conductivity of the material, thereby improving the antistatic performance, and at the same time, the prepared modifier has a porous property, so that it can effectively capture and adsorb water molecules, and the presence of water helps to improve the electrical conductivity of nylon 66 high-strength wire.
[0026] The graphite-like structure and conjugated structure of polyphenylene nanoparticles obtained by high-temperature thermal cracking of phenolic resin have very low hydrogen content, and will not generate toxic and corrosive gases when heated. It can greatly reduce the amount of smoke and has good thermal stability. When burning, there is no black smoke, no dripping, and carbon formation, which improves the combustion behavior of nylon materials. At the same time, after combustion, the polyphenylene particles form a thick protective carbon layer on the surface of the polymer, which reduces the mass transfer and heat transfer between the gas phase and the condensed phase, and improves the flame retardant properties of the obtained nylon 66 high-strength wire. In addition, tannic acid-modified polyphenylene can form a tunnel effect or electron transition to form a conductive path in nylon 66 material through multiple benzene rings and conjugated structures, and the multiple carboxyl and amino structures can make the modifier particles evenly dispersed in nylon 66, and the spacing between particles becomes smaller, so that the conductive carriers can easily migrate, thereby forming a conductive network, and the resistivity is greatly reduced. The obtained nylon 66 high-strength wire has good antistatic properties. At the same time, the molecular structure of tannic acid-modified polyphenylene contains benzene rings, which enables it to form a strong interface bonding force with nylon 66. Good interface bonding can effectively transfer stress, reduce stress concentration, and thus improve the overall mechanical properties of the composite material.
[0027] Compared with directly adding UiO-66 or polyphenylene oxide to nylon 66 slurry and then spinning, the PA66 eight-head spun ultra-high-strength industrial yarn prepared by the present invention has higher mechanical strength and lower thermal shrinkage. The modifier contains rich amino and carboxyl structures, which can form hydrogen bonds with the nylon 66 polymer structure to achieve uniform dispersion, thereby improving the mechanical properties, antistatic properties, and flame retardant properties of the nylon 66 high-strength yarn, having good shape retention, and having good application prospects. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] NHS, N-hydroxysuccinimide; EDC, 1-ethyl-(3-dimethylaminopropyl)carbodiimide.
[0030] Example 1
[0031] This embodiment provides a method for preparing PA66 eight-end spun ultra-high strength industrial yarn, comprising the following steps:
[0032] S1. Preparation of UiO-66-NH2: 0.12 g zirconium tetrachloride and 0.11 g 2-aminoterephthalic acid were added to 50 mL N,N-dimethylformamide, and 2 g acetic acid was added. The mixture was dispersed by ultrasonic stirring at 1000 W for 10 min, and subjected to hydrothermal reaction at 120 °C for 20 h. The mixture was centrifuged, washed, and dried to obtain UiO-66-NH2.
[0033] S2. Preparation of polyphenylene: 0.1 mol phenol, 0.1 mol formaldehyde, and 5 g ammonia water were mixed, heated to reflux and stirred for 2 h, the pH value of the solution was adjusted to 4, the heating reaction was continued for 1 h, 0.5 g zinc chloride was added, heated at 65 ° C, cured for 24 h, thermally cracked at 1100 ° C for 2 h, crushed, and ball milled for 1 h to obtain polyphenylene;
[0034] S3. Preparation of tannic acid-modified polyphenylene: 1 g of polyphenylene was added to 200 mL of water, 0.2 g of tannic acid and 0.05 g of catalyst were added, heated to 40° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain tannic acid-modified polyphenylene;
[0035] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0036] S4. Preparation of modifier: 1 g of tannic acid-modified polyphenylene was added to 100 mL of water, 0.3 g of NHS and 0.2 g of EDC were added, and the mixture was stirred for activation for 20 min, 0.4 g of UiO-66-NH2 was added, the reaction was stirred for 10 h, centrifuged, washed, and dried to obtain a modifier;
[0037] S5. Solid phase viscosity enhancement and humidity control: The nylon 66 spinning grade chips with a relative viscosity of 2.2 were subjected to solid phase viscosity enhancement and humidity control to obtain nylon 66 medium-high viscosity chips with a water content of 650ppm and a relative viscosity of 3.3;
[0038] The solid phase adhesion is carried out at 140°C with nitrogen gas in countercurrent circulation to carry out solid phase adhesion on the slices;
[0039] S6. Melt extrusion spinning: The high viscosity slices of nylon 66 were sent to a screw extruder, a modifier was added, the addition amount was 3wt%, melt extruded at 280°C, filtered, and spun through an eight-head spinning device, and the filament fineness of the ejected filament was 0.05mm;
[0040] S7. Cooling, oiling, drawing and shaping, winding: The filaments are cooled by side blowing to form a tow, oiled, the amount of oil attached is controlled to be 0.5%, drawn and shaped, and wound into a filament tube at a winding speed of 3000m / min to obtain PA66 eight-head spinning ultra-high strength industrial yarn;
[0041] The stretching and shaping is achieved through 1 stage preheating, 2 stages stretching and 2 stages shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 30°C, the temperature of the second pair of hot rollers is 45°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1 times.
[0042] Example 2
[0043] This embodiment provides a method for preparing PA66 eight-end spun ultra-high strength industrial yarn, comprising the following steps:
[0044] S1. Preparation of UiO-66-NH2: 0.17 g zirconium tetrachloride and 0.14 g 2-aminoterephthalic acid were added to 50 mL N,N-dimethylformamide, 3 g acetic acid was added, and the mixture was dispersed by ultrasonic stirring at 2000 W for 20 min, and hydrothermally reacted at 130 ° C for 24 h, centrifuged, washed, and dried to obtain UiO-66-NH2;
[0045] S2. Preparation of polyphenylene: 0.1 mol phenol, 0.12 mol formaldehyde and 7 g ammonia water were mixed, heated to reflux and stirred for 4 h, the pH value of the solution was adjusted to 6, the heating reaction was continued for 3 h, 1 g zinc chloride was added, heated to 75 ° C, cured for 28 h, thermally cracked at 1200 ° C for 4 h, crushed, and ball milled for 1 h to obtain polyphenylene;
[0046] S3. Preparation of tannic acid-modified polyphenylene: 1 g of polyphenylene was added to 200 mL of water, 0.3 g of tannic acid and 0.1 g of catalyst were added, heated to 50° C., stirred for reaction for 5 h, centrifuged, washed, and dried to obtain tannic acid-modified polyphenylene;
[0047] The catalyst is a Tris-HCl solution with a pH of 9.5;
[0048] S4. Preparation of modifier: 1.2 g of tannic acid-modified polyphenylene was added to 100 mL of water, 0.4 g of NHS and 0.3 g of EDC were added, and the mixture was stirred for 40 min for activation. 0.7 g of UiO-66-NH2 was added, and the reaction was stirred for 12 h, centrifuged, washed, and dried to obtain a modifier;
[0049] S5. Solid phase viscosity enhancement and humidity control: The nylon 66 spinning grade chips with a relative viscosity of 2.3 were subjected to solid phase viscosity enhancement and humidity control to obtain nylon 66 medium-high viscosity chips with a water content of 750ppm and a relative viscosity of 3.5;
[0050] The solid phase adhesion is carried out at 170°C with nitrogen gas in countercurrent circulation to carry out solid phase adhesion on the slices;
[0051] S6. Melt extrusion spinning: The high viscosity slices of nylon 66 were sent to a screw extruder, a modifier was added, the addition amount was 5wt%, melt extruded at 300°C, filtered, and spun through an eight-head spinning device, and the filament fineness of the ejected filament was 0.05mm;
[0052] S7. Cooling, oiling, drawing and shaping, winding: The filaments are cooled by side-blown air to form a tow, oiled, the oil content is controlled to be 1.5%, drawn and shaped, and wound into a filament tube at a winding speed of 3800 m / min to obtain PA66 eight-head spinning ultra-high-strength industrial yarn;
[0053] The stretching and shaping is achieved through 1 stage preheating, 2 stages stretching and 2 stages shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 40°C, the temperature of the second pair of hot rollers is 55°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1.01 times.
[0054] Example 3
[0055] This embodiment provides a method for preparing PA66 eight-end spun ultra-high strength industrial yarn, comprising the following steps:
[0056] S1. Preparation of UiO-66-NH2: 0.16 g zirconium tetrachloride and 0.13 g 2-aminoterephthalic acid were added to 50 mL N,N-dimethylformamide, and 2.5 g acetic acid was added. The mixture was dispersed by ultrasonic stirring at 1500 W for 15 min, and hydrothermally reacted at 125 ° C for 22 h. The mixture was centrifuged, washed, and dried to obtain UiO-66-NH2.
[0057] S2. Preparation of polyphenylene: 0.1 mol phenol, 0.11 mol formaldehyde and 6 g ammonia water were mixed, heated to reflux and stirred for 3 h, the pH value of the solution was adjusted to 5, the heating reaction was continued for 2 h, 0.7 g zinc chloride was added, heated to 70 ° C, cured for 26 h, thermally cracked at 1150 ° C for 3 h, crushed, and ball milled for 1 h to obtain polyphenylene;
[0058] S3. Preparation of tannic acid-modified polyphenylene: 1 g of polyphenylene was added to 200 mL of water, 0.25 g of tannic acid and 0.07 g of catalyst were added, heated to 45 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain tannic acid-modified polyphenylene;
[0059] The catalyst is a Tris-HCl solution with a pH of 9;
[0060] S4. Preparation of modifier: 1.1 g of tannic acid-modified polyphenylene was added to 100 mL of water, 0.35 g of NHS and 0.25 g of EDC were added, and the mixture was stirred for activation for 30 min, 0.5 g of UiO-66-NH2 was added, the reaction was stirred for 11 h, centrifuged, washed, and dried to obtain a modifier;
[0061] S5. Solid phase viscosity enhancement and humidity control: The nylon 66 spinning grade chips with a relative viscosity of 2.25 were subjected to solid phase viscosity enhancement and humidity control to obtain nylon 66 medium-high viscosity chips with a water content of 700 ppm and a relative viscosity of 3.4;
[0062] The solid phase adhesion is carried out at 155°C with nitrogen gas in countercurrent circulation to carry out solid phase adhesion on the slices;
[0063] S6. Melt extrusion spinning: The high viscosity slices of nylon 66 were sent to a screw extruder, a modifier was added, the addition amount was 4wt%, melt extruded at 290°C, filtered, and spun through an eight-head spinning device, and the filament fineness of the ejected filament was 0.05mm;
[0064] S7. Cooling, oiling, drawing and shaping, winding: The filaments are cooled by side-blown air to form a tow, oiled, the amount of oil attached is controlled to be 1%, drawn and shaped, and wound into a filament tube at a winding speed of 3500m / min to obtain PA66 eight-head spinning ultra-high-strength industrial yarn;
[0065] The stretching and shaping is achieved through 1 stage preheating, 2 stages stretching and 2 stages shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 35°C, the temperature of the second pair of hot rollers is 50°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1.005 times.
[0066] Comparative Example 1
[0067] Compared with Example 3, the difference is that UiO-66-NH2 is not added.
[0068] The details are as follows:
[0069] S1. Preparation of polyphenylene: 0.1 mol phenol, 0.11 mol formaldehyde and 6 g ammonia water were mixed, heated under reflux and stirred for 3 h, the pH value of the solution was adjusted to 5, the heating reaction was continued for 2 h, 0.7 g zinc chloride was added, heated at 70 ° C, cured for 26 h, thermally cracked at 1150 ° C for 3 h, crushed, and ball-milled for 1 h to obtain polyphenylene;
[0070] S2. Preparation of tannic acid-modified polyphenylene: 1 g of polyphenylene was added to 200 mL of water, 0.25 g of tannic acid and 0.07 g of catalyst were added, heated to 45° C., stirred for reaction for 4 h, centrifuged, washed, and dried to obtain tannic acid-modified polyphenylene;
[0071] The catalyst is a Tris-HCl solution with a pH of 9;
[0072] S3. Solid phase viscosity enhancement and humidity control: The nylon 66 spinning grade chips with a relative viscosity of 2.25 were subjected to solid phase viscosity enhancement and humidity control to obtain nylon 66 medium-high viscosity chips with a water content of 700 ppm and a relative viscosity of 3.4;
[0073] The solid phase adhesion is carried out at 155°C with nitrogen gas in countercurrent circulation to carry out solid phase adhesion on the slices;
[0074] S4. Melt extrusion spinning: The high viscosity slices of nylon 66 were sent to a screw extruder, tannic acid-modified polyphenylene was added in an amount of 4wt%, melt extruded at 290°C, filtered, and spun through an eight-head spinning device, the filament fineness of the spun yarn was 0.05mm;
[0075] S5. Cooling, oiling, drawing and shaping, winding: The filaments are cooled by side-blown air to form a tow, oiled, the amount of oil attached is controlled to be 1%, drawn and shaped, and wound into a filament tube at a winding speed of 3500m / min to obtain PA66 eight-head spinning ultra-high-strength industrial yarn;
[0076] The stretching and shaping is achieved through 1 stage preheating, 2 stages stretching and 2 stages shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 35°C, the temperature of the second pair of hot rollers is 50°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1.005 times.
[0077] Comparative Example 2
[0078] Compared with Example 3, the difference is that no tannic acid-modified polyacene is added.
[0079] The details are as follows:
[0080] S1. Preparation of UiO-66-NH2: 0.16 g zirconium tetrachloride and 0.13 g 2-aminoterephthalic acid were added to 50 mL N,N-dimethylformamide, and 2.5 g acetic acid was added. The mixture was dispersed by ultrasonic stirring at 1500 W for 15 min, and hydrothermally reacted at 125 ° C for 22 h. The mixture was centrifuged, washed, and dried to obtain UiO-66-NH2.
[0081] S2. Solid phase viscosity enhancement and humidity control: The nylon 66 spinning grade chips with a relative viscosity of 2.25 were subjected to solid phase viscosity enhancement and humidity control to obtain nylon 66 medium-high viscosity chips with a water content of 700 ppm and a relative viscosity of 3.4;
[0082] The solid phase adhesion is carried out at 155°C with nitrogen gas in countercurrent circulation to carry out solid phase adhesion on the slices;
[0083] S3. Melt extrusion spinning: The high viscosity slices of nylon 66 were sent to a screw extruder, UiO-66-NH2 was added, the addition amount was 4wt%, and the melt was extruded at 290°C, filtered, and spun through an eight-head spinning device, and the filament fineness of the ejected filament was 0.05mm;
[0084] S4. Cooling, oiling, drawing and shaping, winding: The filaments are cooled by side-blown air to form a tow, oiled, the amount of oil attached is controlled to be 1%, drawn and shaped, and wound into a filament tube at a winding speed of 3500m / min to obtain PA66 eight-head spinning ultra-high-strength industrial yarn;
[0085] The stretching and shaping is achieved through 1 stage preheating, 2 stages stretching and 2 stages shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 35°C, the temperature of the second pair of hot rollers is 50°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1.005 times.
[0086] Comparative Example 3
[0087] Compared with Example 3, the difference is that the polyacene is not modified with tannic acid.
[0088] The details are as follows:
[0089] S1. Preparation of UiO-66-NH2: 0.16 g zirconium tetrachloride and 0.13 g 2-aminoterephthalic acid were added to 50 mL N,N-dimethylformamide, and 2.5 g acetic acid was added. The mixture was dispersed by ultrasonic stirring at 1500 W for 15 min, and hydrothermally reacted at 125 ° C for 22 h. The mixture was centrifuged, washed, and dried to obtain UiO-66-NH2.
[0090] S2. Preparation of polyphenylene: 0.1 mol phenol, 0.11 mol formaldehyde and 6 g ammonia water were mixed, heated to reflux and stirred for 3 h, the pH value of the solution was adjusted to 5, the heating reaction was continued for 2 h, 0.7 g zinc chloride was added, heated to 70 ° C, cured for 26 h, thermally cracked at 1150 ° C for 3 h, crushed, and ball milled for 1 h to obtain polyphenylene;
[0091] S3. Preparation of modifier: 1.1 g of polyphenylene was added to 100 mL of water, 0.35 g of NHS and 0.25 g of EDC were added, and the mixture was stirred for activation for 30 min, 0.5 g of UiO-66-NH2 was added, the reaction was stirred for 11 h, centrifuged, washed, and dried to obtain a modifier;
[0092] S4. Solid phase viscosity enhancement and humidity control: The nylon 66 spinning grade chips with a relative viscosity of 2.25 were subjected to solid phase viscosity enhancement and humidity control to obtain nylon 66 medium-high viscosity chips with a water content of 700 ppm and a relative viscosity of 3.4;
[0093] The solid phase adhesion is carried out at 155°C with nitrogen gas in countercurrent circulation to carry out solid phase adhesion on the slices;
[0094] S5. Melt extrusion spinning: The high viscosity slices of nylon 66 were sent to a screw extruder, a modifier was added, the addition amount was 4wt%, melt extruded at 290°C, filtered, and spun through an eight-head spinning device, and the filament fineness of the ejected filament was 0.05mm;
[0095] S6. Cooling, oiling, drawing and shaping, winding: The filaments are cooled by side-blown air to form a tow, oiled, the amount of oil attached is controlled to be 1%, drawn and shaped, and wound into a filament tube at a winding speed of 3500m / min to obtain PA66 eight-head spinning ultra-high-strength industrial yarn;
[0096] The stretching and shaping is achieved through 1 stage preheating, 2 stages stretching and 2 stages shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 35°C, the temperature of the second pair of hot rollers is 50°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1.005 times.
[0097] Comparative Example 4
[0098] Compared with Example 3, the difference is that the modifier is prepared by mixing 1.1 g of polyacene and UiO-66.
[0099] The details are as follows:
[0100] S1. Preparation of UiO-66: 0.16 g zirconium tetrachloride and 0.13 g phthalic acid were added to 50 mL N, N-dimethylformamide, 2.5 g acetic acid was added, 1500 W ultrasonic stirring was performed for 15 min, hydrothermal reaction was performed at 125 ° C for 22 h, centrifuged, washed, and dried to obtain UiO-66;
[0101] S2. Preparation of polyphenylene: 0.1 mol phenol, 0.11 mol formaldehyde and 6 g ammonia water were mixed, heated to reflux and stirred for 3 h, the pH value of the solution was adjusted to 5, the heating reaction was continued for 2 h, 0.7 g zinc chloride was added, heated to 70 ° C, cured for 26 h, thermally cracked at 1150 ° C for 3 h, crushed, and ball milled for 1 h to obtain polyphenylene;
[0102] S3. Preparation of modifier: 1.1 g of polyphenylene and 0.5 g of UiO-66 were mixed to obtain a modifier;
[0103] S4. Solid phase viscosity enhancement and humidity control: The nylon 66 spinning grade chips with a relative viscosity of 2.25 were subjected to solid phase viscosity enhancement and humidity control to obtain nylon 66 medium-high viscosity chips with a water content of 700 ppm and a relative viscosity of 3.4;
[0104] The solid phase adhesion is carried out at 155°C with nitrogen gas in countercurrent circulation to carry out solid phase adhesion on the slices;
[0105] S5. Melt extrusion spinning: The high viscosity slices of nylon 66 were sent to a screw extruder, a modifier was added, the addition amount was 4wt%, melt extruded at 290°C, filtered, and spun through an eight-head spinning device, and the filament fineness of the ejected filament was 0.05mm;
[0106] S6. Cooling, oiling, drawing and shaping, winding: The filaments are cooled by side-blown air to form a tow, oiled, the amount of oil attached is controlled to be 1%, drawn and shaped, and wound into a filament tube at a winding speed of 3500m / min to obtain PA66 eight-head spinning ultra-high-strength industrial yarn;
[0107] The stretching and shaping is achieved through 1 stage preheating, 2 stages stretching and 2 stages shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 35°C, the temperature of the second pair of hot rollers is 50°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1.005 times.
[0108] Test Example 1
[0109] The performance of the PA66 eight-end spun ultra-high strength industrial yarns prepared in Examples 1-3 of the present invention and Comparative Examples 1-4 was tested, and the results are shown in Table 1.
[0110] Table 1
[0111]
[0112] It can be seen from the above table that the PA66 eight-end spun ultra-high strength industrial yarns prepared in Examples 1-3 of the present invention have good comprehensive properties.
[0113] Test Example 2
[0114] The PA66 eight-end spun ultra-high strength industrial yarns prepared in Examples 1-3 of the present invention and Comparative Examples 1-4 were melt-extruded to prepare standard samples.
[0115] The oxygen index is tested according to GB / T 2406.2-2009 standard.
[0116] The flame retardant rating is tested according to UL-94 standard.
[0117] The results are shown in Table 3.
[0118] Table 2
[0119] Group Limiting oxygen index (%) Flame retardant grade (UL-94) Example 1 33.2 V-0 Example 2 33.9 V-0 Example 3 34.1 V-0 Comparative Example 1 31.3 V-0 Comparative Example 2 26.9 V-2 Comparative Example 3 28.1 V-1 Comparative Example 4 32.0 V-0
[0120] It can be seen from the above table that the PA66 eight-end spun ultra-high strength industrial yarns prepared in Examples 1-3 of the present invention have good flame retardant properties.
[0121] Test Example 3
[0122] The PA66 eight-end spun ultra-high strength industrial yarns prepared in Examples 1-3 of the present invention and Comparative Examples 1-4 were tested for aging resistance and the breaking strength retention rates after various aging tests were tested. The results are shown in Table 3.
[0123] Short-term heat aging: temperature 105°C, duration 408h;
[0124] Short-term wet aging: temperature 70°C, humidity 95±2%, duration 408h;
[0125] Long-term heat aging: temperature 105°C, duration 1000h;
[0126] Long-term wet aging: temperature 70℃, humidity 95±2%, duration 1000h.
[0127] Table 3
[0128]
[0129] It can be seen from the above table that the PA66 eight-end spun ultra-high strength industrial yarns prepared in Examples 1-3 of the present invention have good aging resistance.
[0130] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing PA66 eight-end spinning ultra-high strength industrial yarn, characterized in that: An amino-modified metal organic framework is prepared, coupled with tannic acid-modified polyphenylene, added into molten nylon 66 medium-high viscosity slurry, mixed evenly, melt-extruded and spun, the filaments are cooled by side blowing to form a filament bundle, oiled, drawn and shaped, and wound into a filament tube to obtain PA66 eight-end spun ultra-high strength industrial filament.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: S1. Preparation of UiO-66-NH2: zirconium tetrachloride and 2-aminoterephthalic acid are added to N,N-dimethylformamide, acetic acid is added, ultrasonic stirring is performed to disperse the mixture uniformly, hydrothermal reaction is performed, centrifugation is performed, washing is performed, and drying is performed to obtain UiO-66-NH2; S2. Preparation of polyphenylene: phenol, formaldehyde and aqueous ammonia were mixed, heated to reflux with stirring, the pH value of the solution was adjusted, the reaction was continued by heating, zinc chloride was added, heated to cure, thermally cracked, crushed, and ball-milled to obtain polyphenylene; S3. Preparation of tannic acid-modified polyphenylene: adding polyphenylene to water, adding tannic acid and a catalyst, heating and stirring the reaction, centrifuging, washing, and drying to obtain tannic acid-modified polyphenylene; S4. Preparation of the modifier: adding tannic acid-modified polyphenylene to water, adding NHS and EDC, stirring for activation, adding UiO-66-NH2, stirring for reaction, centrifuging, washing, and drying to obtain a modifier; S5. Solid phase viscosity enhancement and humidity control: The nylon 66 spinning grade chips are subjected to solid phase viscosity enhancement and humidity control to obtain nylon 66 medium and high viscosity chips; S6. Melt extrusion spinning: The high viscosity slices of nylon 66 are sent to a screw extruder, a modifier is added, melt extruded, filtered, and spun through an eight-head spinning device; S7. Cooling, oiling, drawing and shaping, and winding: The filaments are cooled by side-blowing air to form a filament bundle, oiled, drawn and shaped, and wound into a filament tube to produce PA66 eight-end spun ultra-high-strength industrial filament.
3. The preparation method according to claim 2, characterized in that: In step S1, the mass ratio of zirconium tetrachloride, 2-aminoterephthalic acid and acetic acid is 0.12-0.17:0.11-0.14:2-3, the power of ultrasonic stirring and dispersion is 1000-2000W, the time is 10-20min, the temperature of the hydrothermal reaction is 120-130°C, and the time is 20-24h.
4. The preparation method according to claim 2, characterized in that: In step S2, the molar ratio of phenol to formaldehyde is 1:1-1.2, the mass ratio of ammonia water to zinc chloride is 5-7:0.5-1, the heating reflux stirring reaction time is 2-4h, the pH value of the solution is adjusted to 4-6, the heating reaction time is continued to be 1-3h, the heating curing temperature is 65-75°C, the time is 24-28h, and the thermal cracking temperature is 1100-1200°C, and the time is 2-4h.
5. The preparation method according to claim 2, characterized in that: In step S3, the mass ratio of the polyphenylene, tannic acid and catalyst is 10:2-3:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 40-50° C., and the time is 3-5 hours.
6. The preparation method according to claim 2, characterized in that: In step S4, the mass ratio of tannic acid-modified polyphenylene, NHS, EDC and UiO-66-NH2 is 10-12:3-4:2-3:4-7, the stirring activation time is 20-40min, and the stirring reaction time is 10-12h.
7. The preparation method according to claim 2, characterized in that: The relative viscosity of the nylon 66 spinning grade chips in step S5 is 2.2-2.3, the water content of the nylon 66 medium-high viscosity chips is 650-750ppm, and the relative viscosity is 3.3-3.
5. The solid phase viscosity enhancement is performed on the chips at 140-170°C using nitrogen countercurrent circulation.
8. The preparation method according to claim 2, characterized in that: In step S6, the amount of the modifier added is 3-5wt%, the temperature of the melt extrusion is 280-300°C, and the fineness of the filaments sprayed by the spinneret is 0.03-0.05mm.
9. The preparation method according to claim 2, characterized in that: The amount of oil in step S7 is controlled to be 0.5-1.5%; the stretching and shaping is achieved through 1-stage preheating, 2-stage stretching, and 2-stage shaping between six pairs of hot rollers: wherein the temperature of the first pair of hot rollers is 30-40°C, the temperature of the second pair of hot rollers is 45-55°C, the first pair of hot rollers and the second pair of hot rollers preheat the silk strips, and the stretching ratio is 1-1.01 times; the winding speed is 3000-4000m / min.
10. A PA66 eight-end spun ultra-high strength industrial yarn produced by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of high-strength fine-denier super-bright nylon 66 fully-drawn fiber
CN116971040A
Prepn. process of lithium ion cell anode-phosphate / polyphenylpropane composite material
CN1834153A
Method for preparing lithium titanate and lithium titanate / polyacene complex for quick-charged cell material
CN1978524A